Does the longitudinal development of physical and anthropometric characteristics associate with professional career attainment in adolescent Australian footballers?. Issue 4 (August 2020) - Cripps, Ashley J; Banyard, Harry G; Woods, Carl T; Joyce, Christopher; Hopper, Luke S
This study sought to longitudinally and retrospectively determine the relationship between professional career attainment and the development of anthropometric and physical qualities in junior Australian footballers. Eighty adolescent male Australian footballers from a single state academy previously selected onto an under 16 s talent development squad were classified by career attainment (professional team selection; n  = 17 and non-selected; n  = 63). Physical and anthropometric tests were conducted at the end of preseason during participation in under 16 and under 18 competitions. Tests included standing height, mass, stationary countermovement jumps, dynamic vertical jumps, 20-m sprints, agility and 20 m multistage fitness test. Both groups significantly improved all performance measures between the under 16 and under 18 levels. Athletes selected onto a professional team possessed significantly quicker 20-m sprint outcomes than non-selected athletes at both under 16 and under 18 levels, highlighting the importance of this physical capacity within talent development programmes. Binary logistic regression was unable to predict an effect of any measures on career attainment. An inability of the binary logistic regression to identify qualities predictive of long-term career success likely highlights limitations associated with utilising unidimensional models of assessment in talent identification practices. As such, development coaches and sport scientists should be aware that while physical capacities play a role in career attainment outcomes, other factors, such as tactical understanding and technical skill are also likely to be impactful.